Full Stack Application Generation for Insurance Sales based on Product Models - Lima, Carlos Filipe da Silva (2016)
The insurance market is segregated in various lines-of-business such as Life, Health, Property & Casualty, among others. This segregation allows product engineers to focus on the rules and details of a speci c insurance area. However, having di erent conceptual models leads to an additional complexity when a generic presentation layer application has to be continuously adapted to work with these distinct models. With the objective to streamline these continuous adaptations in an existent presentation layer, this work investigates and proposes the usage of code generators to allow a complete application generation, able to communicate with the given insurance product model. Therefore, this work compares and combines di erent code generation tools to accomplish the desired application generation. During this project, it is chosen an existing framework to create several software layers and respective components such as necessary classes to represent the Domain Model ; database mappings; Service layer; REST Application Program Interface (API); and a rich javascript-based presentation layer. As a conclusion, this project demonstrates that the proposed tool can generate the application already adapted and able to communicate with the provided conceptual model. Proving that this autonomous process is faster than the current manual development processes to adapt a presentation layer to an Insurance product model.